2022
DOI: 10.1039/d2dt01302a
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental workings of chemical substitution at the A-site of perovskite oxides— a 207Pb NMR study of Ba-substituted PbZrO3

Abstract: Two-dimensional 207Pb solid-state NMR spectroscopy is employed to determine how the substituent chemistry of perovskite oxides can dictate their antiferroelectric (AFE) or ferroelectric (FE) nature. The analysis of (Pb1-xBax)ZrO3 (PBZ)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Both CSA values indicate bonding environments midway between typical covalent and ionic, , which agrees with the off-center Pb atoms forming covalent bonds only with their closest oxygen neighbors. , Based on these comparisons, it is evident that 207 Pb NMR spectroscopy is highly sensitive to Pb–O bonding. The extracted data are consistent with the average structure reported from diffraction studies, and NMR data consistent with our analysis of PZ have previously been reported. Furthermore, the sharp, well-resolved signals indicate that any structural disorder present in our sample occurs on a much smaller scale than the differences between the two crystallographic sites. ,, While disorder may exist on a local scale, most of the sample is thus well-described by the ordered average structure. This result is in accordance with a previous 207 Pb NMR study which obtained sharp powder line shapes, indicating no random deviations from orthorhombic symmetry and no random Pb displacements in PZ .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Both CSA values indicate bonding environments midway between typical covalent and ionic, , which agrees with the off-center Pb atoms forming covalent bonds only with their closest oxygen neighbors. , Based on these comparisons, it is evident that 207 Pb NMR spectroscopy is highly sensitive to Pb–O bonding. The extracted data are consistent with the average structure reported from diffraction studies, and NMR data consistent with our analysis of PZ have previously been reported. Furthermore, the sharp, well-resolved signals indicate that any structural disorder present in our sample occurs on a much smaller scale than the differences between the two crystallographic sites. ,, While disorder may exist on a local scale, most of the sample is thus well-described by the ordered average structure. This result is in accordance with a previous 207 Pb NMR study which obtained sharp powder line shapes, indicating no random deviations from orthorhombic symmetry and no random Pb displacements in PZ .…”
Section: Resultssupporting
confidence: 88%
“…Instead, we can assume that this average is dominated by the shortest bond (in-plane and out-of-plane) present in the structure. 44,59,60 Additionally, Pb 1 −O bonds are known to be more covalent along the ⟨100⟩ direction, 38,39 which is in accordance with the larger CSA for the Pb 1 site. Both CSA values indicate bonding environments midway between typical covalent and ionic, 40,60 which agrees with the off-center Pb atoms forming covalent bonds only with their closest oxygen neighbors.…”
Section: Combined 3-dimensional Characterization Of Pzmentioning
confidence: 56%
See 2 more Smart Citations
“…(3) Are these interesting entities stable against external electric and thermal fields? So far, most current knowledge of the AFE phenomenon comes from lead-based materials. As the local structures are of paramount importance for the properties of antiferroelectricity and form the basis for the future applications of AFE materials, a systematic study of the atomic structures of lead-free AFE compounds like NN is needed.…”
Section: Introductionmentioning
confidence: 99%